Effect of Continuous and Pulse Microwave on Electrical Conductivity of Glutathione and Zinc Chloride Aqueous Solution - Xueying Li; Chenxi Zhao; Quanlin Guo; Yun Ma; Junxi Zhu; Chaojun Chen; Xianjing Zhang; Lin Wang; Zhengming Tang; Tao Hong; Kama Huang; Dezhi Gou (Bioelectromagnetics in Medicine, 2026)
With the rapid development of communication technology, environmental electromagnetic radiation has also increased sharply. The impact of environmental electromagnetic radiation on human life and health has become more and more concerned. The molecular mechanism of microwave irradiation affecting biomolecular systems remains an unresolved issue. This study investigates the effects of continuous and pulsed microwave irradiation on the conductivity of glutathione-zinc chloride aqueous solutions under varying concentrations, temperatures, and powers. Results show that conductivity is influenced by these factors, with the maximum change rate of 0.328% observed at a 1:5 concentration ratio, 15 W pulsed microwave (10% duty cycle), and 5 ℃. Distinct nonlinear responses between the two microwave modes are attributed to differences in ion polarization behavior, which modulate chelation probability and intermolecular interactions. Molecular dynamics simulations reproduce the experimental trends, validating the results. This work provides insight into the interactions between microwave fields and glutathione-zinc chloride aqueous solutions.